Association of rs2279744 and rs117039649 promoter polymorphism with the risk of gynecological cancer: A meta-analysis of case–control studies. Issue 2 (January 2018) - Zhang, Jianxin; Zhang, Yang; Zhang, Zhenyu
Abstract: Background: Increasing evidence has suggested that rs2279744 is associated with rs117039649 polymorphism, which can increase the risk of gynecological cancers, including cervical, ovarian, breast, and endometrial cancer. The results are inconsistent so that we performed a meta-analysis of current literature to clarify the impacts of these polymorphisms on gynecological cancer. Methods: Eligible articles were identified through an exhaustive search of relevant databases including PubMed, Embase, Web of science, Springer Link, Chinese National Knowledge Infrastructure (CNKI), and Weipu database for the period up to July 2016. Data about the association between single nucleotide polymorphisms (SNPs) and cancer risk were refined from the selected articles as well as other information about cases and controls, and all of them were extracted by 2 independent researchers and pooled odds ratio with 95% confidence interval was calculated. Results: This analysis included 24 articles, 27 case–control studies of rs2279744 polymorphism and 3 case–control studies of rs117039649 polymorphism. Significant association with the risk of gynecological cancer was observed for both SNPs. Subgroup analysis by ethnicity and cancer type (cervical, ovarian, breast, and endometrial) also showed a positive relationship between rs2279744 polymorphism and gynecological cancer risk in Caucasian; and there was also a notable association between rs2279744 polymorphism and cervical cancer. Conclusions: We found that rs2279744 (SNP309) and rs117039649 (SNP285) were both associated with the risk of gynecological cancers. Subgroup analysis showed that rs2279744 (SNP309) was associated with the risk of gynecological cancers in Caucasian and Asian according to the ethnicity and cancer type, especially for endometrial cancer.